Predictors of unmet need for family planning in Ethiopia 2019: a systematic review and meta analysis - Temesgen Getaneh; Ayenew Negesse; Getenet Dessie; Melaku Desta; Tebabere Moltot (BMC, 2020)
Abstract Background unmet need for family planning is a common cause of uninteded pregnancy which mostly end up with abortion. Many studies were conducted on predictors of unmet need of family planning in Ethiopia. But, up until now, single evidence has not been synthesized and various point prevalence estimates of unmet need for family planning have been reported. Therefore, this sytematic review and meta analysis was established to identify the predictors of unmet need for family planning in Ethiopia. Methods search engines including PubMed, Embase, CINAHL, Google Scholar, HINARI portal, and Cochrane Library were used to retrieve included articles and reported using the preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols (PRISMA) checklist guidelines. Joanna Briggs Institute Meta-Analysis of Statistics Assessment and Review Instrument (JBI-MAStARI) was applied for critical appraisal. All observational studies done on reproductive age women and reported on unmet need for family planning were included. Unmet need for family planning is the percentage of women of reproductive age, either married or in a union, who have an unmet need for family planning to stop or delay childbearing. Random effect model was done to estimate the pooled prevalence of unmet need for family planning. Odds ratio with 95% confidence interval was considered to determine the association of identified variables with unmet need of family planning. Cochran's Q statistic, Egger's and Begg's test were carried out to assess heterogeneity and publication bias. Results Fifteen articles and 17, 585 reproductive aged women were included to estimate the pooled prevalence of unmet need for family planning and its predictors in Ethiopia. The prevalence of unmet need for family planning in Ethiopia ranges from 26.52 to 36.39%. Age at first marriage < 18 yrs. with OR = 2.3 (95% CI: 1.08, 4.87), women with no formal education with OR = 1.9 (95%CI: 1.19, 3.04), partner with no formal education with OR = 1.78 (95%CI: 1.18, 2.68) and absence of discussion with their partner about family planning with OR = 3.52 (95%CI, 2.56, 4.87) were predictors of unmet need of family planning in Ethiopia. Conclusion This meta analysis revealed that, the prevalence of unmet need for family planning in Ethiopia was high as compared with the United Nations sphere standard of unmet need for planning, considered to be high if it is greater than 25%. Early marriage, no formal eduaction and lack of discussion with partner on family planning were predictors of unmet need for family planning. Therefore, efforts are needed to empower women through eduaction, avoiding early marriage and facilitating dicussion of partners about family planning in order to improve family planning usage.